2008
DOI: 10.3130/aijs.73.1019
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study for Drying Shrinkage of Ready-Mixed Concrete and Stochastic Ivestigation

Abstract: This study focused to clarify the status of drying shrinkage in ready-mixed concrete via field study using simplified drying shrinkage testing method, which has not been sufficiently examined. The field study results revealed that significant variation in drying shrinkage properties for ready-mixed concrete. Furthermore, stochastic investigation for the field data demonstrated dominant influence of coarse aggregate type on drying shrinkage compared with other parameters like unit water content and led to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…There are many factors which affect concrete drying shrinkage. Recently, among the constituent materials of concrete, it has been reported that the type of coarse aggregate is one of the most dominant factors which affect drying shrinkage of concrete 1) . We have demonstrated that the mean value of the coarse aggregate drying shrinkage strain measured by using wire strain gauges and concrete drying shrinkage strain are high mutually related 2) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many factors which affect concrete drying shrinkage. Recently, among the constituent materials of concrete, it has been reported that the type of coarse aggregate is one of the most dominant factors which affect drying shrinkage of concrete 1) . We have demonstrated that the mean value of the coarse aggregate drying shrinkage strain measured by using wire strain gauges and concrete drying shrinkage strain are high mutually related 2) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we investigated the relationship between the drying shrinkage strain of concrete and the calculated Youngs modulus of coarse aggregate, and considered the applicability of estimation by composite model by using the initial tangent modulus or the secant modulus for coarse aggregate. The composite model which has been proposed by KISHITANI & BABA 6) is written as equation (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…could be used to uniformly express coarse aggregate and concrete drying shrinkage strain. The average pore size r (nm) can be obtained from equation (1).…”
Section: Concretementioning
confidence: 99%
“…Among the constituent materials of concrete, it has been reported that the most dominant factor is the type of coarse aggregate 1) . In the past we have focused on the shrinkage properties of the coarse aggregate, investigating the validity of measuring the drying shrinkage strain using wire strain gauges.…”
Section: Introductionmentioning
confidence: 99%